2016
DOI: 10.4103/0253-7613.194863
|View full text |Cite
|
Sign up to set email alerts
|

Seizure following chemotherapy (paclitaxel and cisplatin) in a patient of carcinoma cervix

Abstract: Cisplatin and paclitaxel both can cause peripheral neurotoxicity as an adverse effect; however, central nervous system neurotoxicity in the form of seizures is rare. We report a case of a 36-year-old female patient of metastatic carcinoma cervix, who developed seizure shortly after cisplatin infusion. Her laboratory investigations were within normal limits. Computed tomography scan and magnetic resonance imaging of the brain did not reveal brain primary metastasis or meningeal carcinomatosis. She had no compla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, we discovered that GADD45A interacts with genistein and cisplatin. Genistein has been implicated in antiepileptic effects [ 42 , 43 ], while cisplatin has been reported to induce seizures [ 44 , 45 ]. Therefore, the results of the PPI networks and drug–gene interaction further underscore the significant role of GADD45A in epilepsy therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we discovered that GADD45A interacts with genistein and cisplatin. Genistein has been implicated in antiepileptic effects [ 42 , 43 ], while cisplatin has been reported to induce seizures [ 44 , 45 ]. Therefore, the results of the PPI networks and drug–gene interaction further underscore the significant role of GADD45A in epilepsy therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The neurotoxicity mostly affects the peripheral nervous system. It can be explained by the higher susceptibility of platinum drugs to access the dorsal root ganglia and peripheral nerves, in comparison to the central nervous system (CNS) [ 7 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, cisplatin-induced encephalopathy is diagnosed using a multidisciplinary approach that includes clinical, radiological, and biological criteria. We must take into account the occurrence of neurological symptoms shortly following cisplatin infusion and rule out the other causes of encephalopathy in patients with cancer such as brain metastases, infectious causes, cerebral hemorrhage, and metabolic disorders (hyper/hypoglycemia, hyper/hypocalcemia, hyper/hyponatremia, azotemia) [ 5 , 8 ]. The improvement in symptomatology a few days after discontinuing therapy further supports the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…This complication can occur at the end of CDDP chemotherapy; despite the severity of this clinical syndrome, the majority of the patients make a full recovery (Steeghs et al, 2003; Zahir et al, 2012; Kabre and Kamble, 2016). Focal neurological deficits or a decreased level of consciousness, with or without seizures, has been described (Berman and Mann, 1980; Mead et al, 1982; Gorman et al, 1989; Brauers et al, 1997; Fuse-Nagase et al, 1997; Chue et al, 2009; Rohitashwa et al, 2016). Holman et al reported a case of SE associated with CDDP in a 54-year-old patient with recurrent cervical carcinoma without other underlying medical conditions (Holman et al, 2015).…”
Section: Discussionmentioning
confidence: 99%